Is the impact of loggings in the last primeval lowland forest in Europe underestimated? The conservation issues of Białowieża Forest. (November 2018) - Mikusiński, Grzegorz; Bubnicki, Jakub Witold; Churski, Marcin; Czeszczewik, Dorota; Walankiewicz, Wiesław; Kuijper, Dries P.J.
Abstract: Loggings in biodiversity hot-spots are perceived as very serious threat to forest species and habitats of high conservation interest. In this paper we scrutinize the spatial impacts of recent loggings in the Polish part of the renowned Białowieża Forest being the last remaining area of lowland temperate forest with a primeval character in Europe with the status of World Heritage and Natura 2000 site. The loggings have been applied in order to cope with the outbreak of the spruce bark beetle Ips typographus . We used satellite images to perform cover change detection analysis that delineated areas being logged in Białowieża Forest between July 2015 and June 2018. Next, we assessed the extent of forest loss in areas with different management regimes as well as landscape-scale impacts. The total area of detected clear-cuts amounted to at least 675 ha, including 229 ha of old-growth stands. Assuming a buffer of 100 m from the edge of cleared forest patches, the cumulative direct and indirect impact of recent logging activities was estimated to amount to at least 4073 ha of affected forest. Logging activities resulted in a 26% increase in fragmentation in the entire Natura 2000 area. We argue that the ecological impact of logging extends beyond the logged areas by modifying the landscape structure and affecting ecosystem functioning on a landscape scale. As such, the recent salvage loggings in the Białowieża Forest clearly damaged the conservation value of this precious area, not in the least by increasing its fragmentation. To avoid further degradation, we strongly argue for allowing natural tree regeneration on clear cuts and also for the extension of Białowieża National Park to cover the entire forested area. Highlights: The renowned Białowieża Forest has recently been partially salvage-logged in response to a spruce bark beetle outbreak Using satellite images we quantified the total logged area to be at least 675 ha including 229 ha of old-growth forests Assuming a buffer of 100 m we argue the cumulative impact of logging to amount to at least 4073 ha of affected forest This has negative consequences for biodiversity but also affects ecosystem functioning by a 26% increase in fragmentation To prevent further degradation, natural processes should shape the entire Białowieża Forest by enlarging the national park